PENGARUH PENERAPAN MODEL COGNITIVE APPRENTICESHIP TERHADAP KREATIVITAS KEPRIBADIAN SISWA KELAS XI ADMINISTRASIÂ PERKANTORAN SMKN 1 SURABAYA - NIKMAH, ULFATUN (Jurnal Mahasiswa Teknologi Pendidikan, 2017)
Cognitive apprenticeship model is guided model by the expert in the field and it leads the students to the interdependent learning dichotomy between in the classroom and the real life. This model have several methods such as modeling, coaching, scaffolding, articulation, reflection and exploration. The problem from  students during the learning practice of handcraft material were still in the stage of making the product. They had not been able to do the proper packaging yet and the product had not reached worth selling yet. Entrepreneurship lesson by training the students’ creative expression skill to put their thoughts and ideas by considering their impact on ecosystems, management and economics. Thus, this study aims to increase students’ creativity in making the handcraft and able to analyze the work to describe the material applied. The method used in this research is quantitative experiments with Experimental Design Matched Group Comparison. Based on data analysis (F) with anava one way formula that theresults of  personal creativity is Fcount>Ftable (6.289> 4.85) and analysis data in the results of product creativity (7,019> 4.85). Therefore, the result of this study is that the cognitive apprenticeship model that there is a significant differences on the application of learning model Cognitive Apprenticeship in the learning process. Keywords:  Cognitive Apprenticeship Model, creativity, entrepreneurship.